Fairness, flexibility and the far right: Understanding the relationship between populism, social spending and labor markets - Andreas Bergh; Anders Kärnä (Research Institute of Industrial Economics (IFN), 2021)
The large increase in economic inequality and the dismantling of the welfare state in Western democracies has been connected to the rise of populist parties. If populist voting is explained by fear and labor market insecurity and if people care more about procedural fairness than inequality of economic outcomes, national income inequality should be less important than other factors in explaining vote shares of populist parties. Using election results from 33 European countries over the 1980-2018 period, two different classifications of populist parties and three different measures of government/welfare state size, we find no relationship between country-level economic inequality, as measured by the disposable income Gini, and either right-wing or leftwing populism. An alternative hypothesis that right-wing populism is dampened by labor market flexibility and social spending is developed and shown to have empirical support.
Keywords: P16; D63; D31; 330; Inequality; Populism; The welfare state; Social spending; Employment protection